Effect of combinations of chemical fertilizers and poultry manure on the productivity of crops in the cauliflower-stem amaranth-jute pattern (Bangladesh Journal of Agricultural Research, 2010)
Different combinations of chemical fertilizers and organic manure were applied for sustainable crop productivity in the cauliflower-stem amaranth -jute cropping pattern. The experiment was conducted at farmer’s field in Multilocation Testing (MLT) site of Pakshi, Pahna over three years. There were five combinations of chemical fertilizers (CF) and poultry manure (PM) along with absolute control arranged in a randomized complete block design. The results revealed that all three crops showed significant yield for fertilizer and poultry manure use. Higher yields were obtained with 50% CF + 50% PM followed by 75% CF + 25% PM treatments where cauliflower equivalent yield was increased by 85% and 78%, respectively, over control. This indicates a positive residual effect of poultry manure on the subsequent crops. From the economic points of view, the highest marginal benefit cost ratio (MBCR) was attained in 100% chemical fertilizer due to its lower variable cost followed by 75% CF + 25% PM treated plots. However, gross margin was higher in 50% CF + 50% PM combination for its higher total yield. Key Words: Chemical fertilizer; poultry manure; productivity. DOI: 10.3329/bjar.v34i1.5761Bangladesh J. Agril. Res. 34(1) : 113-121, March 2009